The awareness among degree student at UiTM Puncak Alam toward Takaful V Conventional Insurance / Nur Fazlin Ghazali - Ghazali, Nur Fazlin (Academy of Contemporary Islamic Studies (ACIS), 2017)
Background of study: This study was proposed to explore student’s understanding and knowledge about takaful, this study also proposed to measure the level of awareness among students and to know their preference between Islamic insurance and conventional insurance. This is because students are young generation that will lead this country, as an educated people, they must know about halal and haram all activities in daily life. This study will explore deeper their knowledge if they are understand about takaful operation or if they will able to compare between takaful and conventional insurance and make the best choice as an investment for the future. Method: In this study, both qualitative and quantitative method will be used. The qualitative study with semi structured interview and also the research from a library will be apply. In quantitative study, 50 set of questionnaires will be given to selected respondents randomly in Uitm Puncak Alam among the degree students. It means that stratified sample is used in this study. And also, 5 students also was selected to interviews face to face to know their opinion. Data was then subjected to framework analysis. Result: 5o respondents were given the questionnaires and 5 respondents were interviewed. Their age ranged from 19-25 years old. All of them are Malays and Muslim. Most of the respondents that were given a questionnaire do not sure about takaful and its operation. Only few of them manage to explain about modus operandi in takaful, concept and features. Conclusion: Most of students do not aware about the important of takaful and they are not exposed with the information about takaful. Takaful companies should take an action to spread the information to students in University level.